Effects of a large-scale and offshore marine protected area on the demersal fish assemblage in the Southwest Atlantic - Alemany, Daniela (2013)
There are few extensive and offshore located marine protected areas (MPAs) in the world oceans and their performance is still being debated. We evaluated the effects of a large-scale offshore MPA located on the Southwest Atlantic Patagonian Shelf (43°S 63°W) on the demersal fish assemblage. Compliance of the Patagonian MPA was assessed by analysing eight years of satellite vessel monitoring system (VMS; 2000–2008) data, which showed compliance and fishing effort concentrated near the protection boundaries. MPA effects were studied by employing a five year database collected by a scientific research vessel in protected and fishing locations, before and after the MPA establishment. We assessed 152 scientific trawling stations using multivariate analysis of fish assemblage structure, fish abundance (discriminating target and non-target species), and mean size and proportion of juveniles of the target species (Argentine hake, Merluccius hubbsi). The identified MPA effects were a trend towards increasing abundance of the demersal fish assemblage, the target and non-target fish species, and hake juvenile size, and a higher proportion of juveniles aged 2+ inside the MPA. These positive trends support the case for offshore, large-scale MPAs.